Acupuncture’s Immunomodulatory Effects on Macrophages in Allergic Disorders: A Systematic Review - Qu Y; Gu Y; Zhang X; Wang Y; Xing X (Journal of Asthma and Allergy)
Yang Qu,1 Yunhe Gu,2 Xiaoying Zhang,1 Yanlong Wang,3 Xueliang Xing1 1The Second Affiliated Hospital of Heilongjiang University of Chinese Medicine, Harbin, Heilongjiang, 150001, People’s Republic of China; 2The First Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang, 150006, People’s Republic of China; 3The second Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang, 150086, People’s Republic of ChinaCorrespondence: Xueliang Xing, The Second Affiliated Hospital of Heilongjiang University of Chinese Medicine, Harbin, Heilongjiang, 150001, People’s Republic of China, Email Xingyi918@126.comAbstract: The incidence of allergic diseases has been increasing annually, severely affecting the quality of life of patients. With the growing recognition of traditional medicine, acupuncture, an ancient Chinese therapeutic method, has gradually gained attention for its potential in immune modulation. Studies have shown that macrophages play a crucial role in the development of allergic diseases, and acupuncture may influence allergic reactions by modulating the function of macrophages. This article aims to systematically evaluate the regulatory effects of acupuncture on macrophages in allergic diseases and the corresponding mechanisms. It analyzes existing research findings and explores the clinical application prospects of acupuncture in this context. By understanding how acupuncture affects the activation, secretion, and role of macrophages in immune responses, we hope to provide new insights and directions for the treatment of allergic diseases.Keywords: acupuncture, macrophages, allergic diseases, immune regulation, allergic asthma, allergic rhinitis, allergic skin diseases